PVDF microspheres@PLLA nanofibers-based hybrid tribo/piezoelectric nanogenerator with excellent electrical output properties. Issue 18 (20th August 2021) - Li, Xuan; Yu, Wenguang; Gao, Xuefeng; Liu, Haihui; Han, Na; Zhang, Xingxiang
Abstract : An efficient energy-harvesting hybrid tribo/piezoelectric nanogenerator (HTPENG) with an innovative structure of "microspheres@nanofibers" was developed to drive miniaturized portable electronic devices. Abstract : Meeting the ever-increasing demand for portable, sustainable, and renewable nanogenerators that can convert mechanical energy into electricity is a key research issue. Therefore, to compensate for deficiencies in piezoelectric nanogenerators (PENGs) and triboelectric nanogenerators (TENGs), an efficient energy-harvesting hybrid tribo/piezoelectric nanogenerator (HTPENG) with an innovative structure of "microspheres@nanofibers" was developed to drive miniaturized portable electronic devices. Owing to its unique structure, the as-fabricated HTPENG manifested excellent electrical output properties. The short-circuit current, the open-circuit voltage and the power density of the HTPENG were 8.066 μA, 35.693 V, and 525.12 mW m −2, respectively, which are enough to light up a light-emitting diode in 20 seconds. It is expected that this research can provide new methods to enhance the electrical output properties of nanogenerators and stimulate new ideas for the structural design of nanogenerators in the future.